APLICAÇÃO DA METODOLOGIA DE AVALIAÇÃO DE PERDAS E DANOS (DALA) NO BAIRRO VILA AMÉRICA NO MUNICÍPIO DE SANTO ANDRÉ - Viadana, Tazio; Nogueira, Fernando; Abiko, Alex (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Disasters occur by natural processes of the dynamics of the environment or as a result of human actions. These events cause not only impact to the community, but also on the economy of the affected regions. To scale these disasters are used valuation methods losses and damages caused by the disaster. In this context, this work aims to apply the methodology DAlA (Damage and Loss Assessment), a municipality, compare the final result with the Gross Domestic Product of the city, making a reflection on the measures adopted in repairing the damage. The study area is within the Greate ABC region was defined as the frequent floods that cause significant disasters in the summers from 2012 to 2014.